Digital Payment System Transformation For Msmes: A Systematic Literature Review - Kartono Kartono; Sudiarto Sudiarto; Yan Kristian Halomoan (Doctoral Program of Social Science Pasundan University, 2026)
This study aims to analyze the development of digital payment systems implemented by MSMEs and identify factors influencing the success of digital payment system transformation in MSMEs based on a systematic literature review. This study uses a descriptive exploratory approach using a literature review approach or library research, namely referring to various literature, such as books, dissertations, scientific journals and the internet. The results of the literature review indicate that the development of digital payment systems in Indonesia has progressed rapidly through the transformation of cash to non-cash payments, particularly with the implementation of QRIS, which supports the creation of an inclusive digital economic ecosystem. In addition, the success of digital payment system transformation in MSMEs is influenced by internal factors, such as ease of use, transaction speed, system security, and digital literacy of business actors, as well as external factors, including digital infrastructure support, government policies, and digital technology developments. The synergy of these factors makes digital payment systems an important instrument in increasing the efficiency, competitiveness, and sustainability of MSMEs in the digital era.